Dysfunctional Metacognitive Beliefs Are Associated with Decreased Executive Control - Kraft, Brage; Jonassen, Rune; Stiles, Tore C.; Landrø, Nils. I. (Frontiers in Psychology, 2017)
Dysfunctional metacognitive beliefs (‘metacognitions’) and executive control are important factors in mental disorders such as depression and anxiety, but the relationship between these concepts has not been studied systematically. We examined whether there is an association between metacognitions and executive control and hypothesised that decreased executive control statistically predicts increased levels of metacognitions. Two hundred and ninety-nine individuals recruited from the general population and outpatient psychiatric clinics completed the Metacognitions Questionnaire-30 and three subtests from the Cambridge Neuropsychological Test Automated Battery corresponding to the three-component model of executive functions. Controlling for current depression and anxiety symptoms, decreased ability to shift between mental sets was associated with increased negative beliefs about the uncontrollability and danger of worry and beliefs about the need to control thoughts. The results suggest a basic association between metacognitions and executive control. Individual differences in executive control could prove important in the personalisation of metacognitive therapy.